An algorithm for text detection and character recognition of the Baybayin script - Mercado, Tamara Cher R. (Southeastern Philippines Journal of Research and Development, 2014)
This study is about the development of a system that converts Baybayin script, the writing system of Filipinos during the pre-Spanish era and considered one of the ancient scripts that faced extinction into Latin through optical character recognition. After detection and recognition, it formed the recognized characters into syllables and words, represented by Latin characters, which serve as the output of the system. Text detection was done using horizontal and vertical projection while the recognition of the character was done through template matching. Based on the results, template matching gave 85-95 percent average in highest matched percentage obtained from each character. This value resulted to an accuracy recognition rate at a range of 85-100 percent for text with size higher than 70 points. Horizontal projection, vertical projection and template matching were the core algorithms used in the system.